2020
DOI: 10.1002/stem.3196
|View full text |Cite
|
Sign up to set email alerts
|

Signature quality attributes of CD146+ mesenchymal stem/stromal cells correlate with high therapeutic and secretory potency

Abstract: CD146 + bone marrow-derived Mesenchymal Stem/Stromal Cells (BM-MSC) play key roles in the perivascular niche, skeletogenesis and hematopoietic support, however elucidation of therapeutic potency has yet to be determined. Here, inflammatory challenge to crude BM-MSC captured a baseline of signatures including enriched expression of CD146 + with CD107a + , CXCR4 + , and LepR + , transcriptional profile, enhanced secretory capacity, robust secretome and immunomodulatory function with stimulated target immune cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 88 publications
3
63
0
1
Order By: Relevance
“…Collectively, these data demonstrate the reinforcing effect of spheroid culturing on IFP-MSC propensities even in non-induced cultures without any exogenous pro-inflammatory/pro-fibrotic priming. Upon CD146-based selection, the generated subpopulations showed distinct protein, molecular and secretory profiles, similar to our previous report with BM-MSC [30]. As highlighted in our previous reports CD146 and CD10 are both key molecules correlated with increased immunomodulatory MSC functionality [27-IFP-MSC spheroids reverse synovitis/IFP fibrosis 29].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Collectively, these data demonstrate the reinforcing effect of spheroid culturing on IFP-MSC propensities even in non-induced cultures without any exogenous pro-inflammatory/pro-fibrotic priming. Upon CD146-based selection, the generated subpopulations showed distinct protein, molecular and secretory profiles, similar to our previous report with BM-MSC [30]. As highlighted in our previous reports CD146 and CD10 are both key molecules correlated with increased immunomodulatory MSC functionality [27-IFP-MSC spheroids reverse synovitis/IFP fibrosis 29].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, we have also recently reported that a similar inflammatory cell priming protocol applied to bone marrow-derived MSC (BM-MSC) enriches the preparation in CD146 + cells, unveiling a subset with innately higher immunomodulatory and secretory capacities compared to their CD146counterparts [30]. A comparable CD146-dependent phenotypic and functional discrimination in IFP-MSC has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…This results match with a study showing that CD146 + BM-MSCs showed greater immunomodulatory functions upon in ammatory priming compared to CD146 -BM-MSCs. 94 We also noticed that FL-MSCs contained both CD271 bright , and CD271 low cells, while adult BM-MSCs cultures contained only CD271 low cells. This nding is consistent with previous studies demonstrating that CD271 high cells have a much higher clonogenic capacity than CD271 low cells, [76][77][78] and with our data showing that when seeded in a strictly identical initial number, FL-MSCs proliferate more than BM-MSCs with an effect discernible from day 2.…”
Section: Discussionmentioning
confidence: 51%
“…In fact, it has been proposed that MSC can indeed promote M2 macrophage polarization in vitro (Harrell et al, 2019). Furthermore, our group recently reported the switch of IFP macrophages from an M1 to an M2 phenotype in vivo, after a single intra-articular injection of a subset of BM-MSC (CD146 + ) in rats with induced synovitis and IFP fibrosis (Bowles et al, 2020).…”
Section: Msc-induced Immunomodulation: Focus On Macrophage Polarizationmentioning
confidence: 89%